Examining Occupational Stress and its Related Factors in Nurses Working in the Educational Hospitals of Kashan University of Medical Sciences - Hamidreza Gilasi; Fatemeh Mohebbi; Najmeh Sharifi (Iranian Journal of Nursing and Midwifery Research)
Background: Long-term occupational stress can lead to an increase in clinical errors and negative effects on nurses’ health. This study aims to investigate occupational stress and its related factors in nurses working in the educational hospitals of Kashan University of Medical Sciences. Materials and Methods: This cross-sectional study was conducted at Kashan University of Medical Sciences in 2019, in which 350 nurses were selected by stratified random sampling. Demographic information and Hospital job Stress Assessment questionnaire (HSS) were two parts of the questionnaire. The data were analyzed using the SPSS 22 software. For statistical analysis, background variables were described first. Independent t-tests, ANOVA, and their nonparametric equivalents or regression models were used to investigate the relationship between the occupational stress and background variables. The correlation coefficient was then used to assess the relationship between the quantitative variables. Results: The results showed that the stress level of 87.71% of the nurses was at a severe level, while 12.30% of at the nurses experienced a moderate level. The total stress score was higher among women than among men, and the difference was statistically significant (t348= -3.39, p = 0.001). A weak and nonsignificant negative correlation was observed between the total stress score with age (r = -.0.06, p = 0.26) and work experience (r = -0.076, p = 0.15). Conclusions: Considering that most of the nurses had a high level of stress, and while occupational stress plays an important part in people’s life, it seems necessary to plan to reduce the level of the occupational stress in the nurses.